Socio-economic changes in agriculture in the Kaballokang Pakkabba village community, Takalar - Rahman, Abdul (Jurnal Ekonomi dan Riset Pembangunan, 2026)
This research examines the socio-economic transformations of the farming community in Kaballokang Pakkabba Village, Takalar Regency. The shift from traditional farming systems toward modernization and commercialization has triggered significant changes in the local social structure. Economically, these changes are evident in increased productivity through the adoption of modern agricultural machinery (alsintan) and high-yield seed varieties, which have reshaped household income patterns. Socially, however, modernization has led to a shift in traditional values, where the long-standing communal practices of sipakatau and sipalele are increasingly replaced by contractual, wage-based labor relations. Furthermore, reliance on chemical inputs and market price fluctuations poses new challenges to farmers' welfare. The findings indicate that while there is an improvement in material living standards, there is also a growing social vulnerability as traditional cohesion fades. This study concludes that the socio-economic changes in Kaballokang Pakkabba represent an adaptive response to agricultural modernization, which demands efficiency at the expense of local cultural values